THE REPRESENTATION OF THE HOLOCAUST IN JOHN BOYNE'S THE BOY IN THE STRIPED PYJAMAS - Setiawan, Heru (2012)
The study was concerned with the issue of the Holocaust in the novel "The Boy in the Striped Pyjamas". The aim of this research is to identify the ways in which the story tells the events of the Holocaust in World War II which contains harsh things for children readers.There are four ways of the story tells the events of the Holocaust for children readers as proposed by Eva Tal (2004). First, finding an appropriate representation of death and suffering. The taboos in presenting horror, violence, and death are broken through the narrative structure. The story begins in a happy time and before the disruption of the main character's life. The conflict or the climax of the story is revealed by the use the young character's disguised understanding of the events of the Holocaust such as the suffering, in order to make children readers secure when they enter the conflict of the story which contains the issue of the Holocaust. Second, designing happy endings for children. However, the book does not exactly reveal happy ending, rather it is closed by psychological closure which brings protagonist's personal conflict into balanced, and the structural closure is denied in the story. Third, telling the story from a child's point of view. There's an indication of incomprehension of the main character toward particular issue, which means the incomprehensibility toward the catastrophe which exists in the story. Fourth, the story uses symbolism and figurative language to portray death rather than full elaboration of the death. Moreover, the story uses repetition of words. It has a function to make children readers feel secure and comfortable when they read the story which basically contains harsh issue, the Holocaust. The ways that the author employs in the story are in order to protect them from the full horror of the Holocaust. Such actions are based on the assumption that children are too fragile to comprehend horrible thing and they should not be exposed to the events. Moreover, the story represents the real horror of events of the Holocaust by using softened language and avoiding harsh words.